Wheat Cost-Return Budget (W-F Rotation) in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M. (My University, 1999)
This publication contains information for a projected budget reflecting expected income and cost based on wheat-fallow rotation practices in western Kansas.
MF257_1999-10
Keywords: MF257; Economics; Crops; MF